POSSIBLE INFLUENCE OF THE BLOCK STRUCTURE OF THE CRUST ON THE SIZE DISTRIBUTION OF SOCIOPOLITICAL SUBDIVISIONS - Sukhonos S.I. (My University, 1988)
We analyze the average size distribution of sociopolitical divisions (countries, provinces, states and the like) in the light of the phenomenon of 'dominant' dimensions of the hierarchical block structure of the crust. Data from several reference works were used to develop a size distribution table of countries of the world and of internal subdivisions of the largest countries in the scale range from 10 to 108 km2. Some of the distributions are plotted to show that the data from all continents exhibit a multimodel distribution, with two pronounced modes: the first in the interval (1 to 5)· 104 km, and the second in the interval (1 to 5)·105 km, separated by a statistically significant minimum frequency of occurrence of countries and regions with areas of (5 to 10)·104 km.